Ethnobotany of Sterculia foetida L. Samawa Ethnic Communities in Sumbawa Regency, West Nusa Tenggara - Arya Arismaya Metananda; Ervizal AM Zuhud; Agus Hikmat; Nurul Qomar; Defri Yoza; Niskan Walid Masruri; Viny Volcherina Darlis (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2022)
Sterculia foetida L. is multipurpose plant which began endangered. Information on ethnobotanical studies or knowledge and use of this species is still limited. This research is structured to answer this problem. By using the method of interviewing community leaders in Sumbawa, this study found that local wisdom related to Sterculia foetida L. is quite diverse. Good knowledge as well as the use of Sterculia foetida L. found among others for food, medicine, bio-fuel, jewelry, building materials, traditional ceremonies, handicrafts, traditional games and environmental services. Information on the benefits of Sterculia foetida L. should be disseminated. It is hoped that the ethnobotanical study of Sterculia foetida L. can be a good start to support Sterculia foetida L. conservation in the future.